2014
DOI: 10.1086/674903
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone Normalizes Phosphodiesterase‐5 Activity in Pulmonary Artery Smooth Muscle Cells from Lambs with Persistent Pulmonary Hypertension of the Newborn

Abstract: Phosphodiesterase-5 (PDE5) is the primary phosphodiesterase in the pulmonary vasculature. It degrades cyclic guanosine monophosphate (cGMP) and inhibits cGMP-mediated vasorelaxation. We previously reported that hydrocortisone treatment decreased hyperoxia-induced PDE5 activity and markers of oxidative stress in lambs with persistent pulmonary hypertension of the newborn (PPHN) ventilated with 100% O 2 . The objective of our study was to determine the molecular mechanism by which hydrocortisone downregulates PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Steroids have been reported to decrease hospital stay and duration of oxygen use in infants with meconium aspiration [ 130 , 131 ]. It is proposed that hydrocortisone attenuates ROS production by induction of superoxide dismutase and normalization of PDE5 activity [ 132 ]. Looking at the evidence this far, we do not recommend routine use of steroids in patients with PPHN especially if there is suspicion of viral or bacterial sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Steroids have been reported to decrease hospital stay and duration of oxygen use in infants with meconium aspiration [ 130 , 131 ]. It is proposed that hydrocortisone attenuates ROS production by induction of superoxide dismutase and normalization of PDE5 activity [ 132 ]. Looking at the evidence this far, we do not recommend routine use of steroids in patients with PPHN especially if there is suspicion of viral or bacterial sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with 1 mg/kg HC resulted in significant decreases in vascular PDE5 activity (40±13% vs. hyperoxia-vehicle) ( Figure 7 , panel A). We then examined the effects of HC on PDE5 activity in isolated mouse PASMC to determine if HC was acting specifically on the smooth muscle as we have previously described ( 20 , 21 ). 24h exposure of isolated PASMC to 95% O 2 increased PDE5 activity (244±47% vs. 21% untreated) ( Figure 7 , panel B) while treatment with 100nM HC significantly attenuated that activity (34±10% vs. 95% untreated) ( Figure 7 , panel B).…”
Section: Resultsmentioning
confidence: 99%
“…Our lab has previously demonstrated that postnatal hydrocortisone improves oxygenation, attenuates oxidative stress, and decreases hyperoxia-induced PDE5 activation in a sheep model of PPHN ( 20 ). In addition, hydrocortisone treatment of isolated pulmonary artery smooth muscle cells (PASMC) attenuated PDE5 activity induced by 24hr hyperoxia exposure ( 21 ). In the current study we set out to determine the effects of hydrocortisone on pulmonary vasculature, lung architecture, and vascular PDE5 activity in a mouse model of hyperoxic lung injury, which more closely approximates the preterm pulmonary vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence derived from animal models of PPHN suggests a potential role for glucocorticoids in restoring normal pulmonary vascular function. In the lamb model of PPHN induced by ductal ligation, hydrocortisone significantly improved arterial-to-alveolar ratios and attenuated oxidative stress, in part by increasing SOD activity 29, 30 . Hydrocortisone increased cGMP by normalizing sGC and PDE 5 activity and by attenuating abnormalities induced by oxidative stress.…”
Section: Pulmonary Vasodilators Acting Via the Cgmp Pathwaymentioning
confidence: 91%